The use of an upper extremity hemodialysis access site for stenting of the superior mesenteric artery for chronic mesenteric ischemia - Mobeen Farooq, MD; Craig Greben, MD; Larry Frankini, MD; Eric Gandras, MD (Journal of Vascular Surgery Cases and Innovative Techniques, 2019)
We report the use of an upper extremity hemodialysis access site to facilitate endovascular treatment of the superior mesenteric artery in the setting of chronic mesenteric ischemia. A 64-year-old woman with end-stage renal disease on hemodialysis presented with worsening symptoms associated with chronic mesenteric ischemia. Her left upper extremity interposition graft within the fistula access site was selected to avoid a hostile aortoiliac system and in consideration of the potential benefits it provided over transfemoral, transbrachial, and transradial sites. The procedure was technically successful without complication. Hemodialysis access sites, such as the interposition graft within the fistula of this patient, are a potential route of upper extremity access for mesenteric interventions in patients with end-stage renal disease on hemodialysis. Keywords: End-stage renal disease, Hemodialysis, Hemodialysis access site, Arteriovenous graft, Chronic mesenteric ischemia, Superior mesenteric artery stent